Asymptomatic Infection and Transmission of Pertussis in Households: A Systematic Review. (29th June 2019) - Craig, Rodger; Kunkel, Elizabeth; Crowcroft, Natasha S; Fitzpatrick, Meagan C; de Melker, Hester; Althouse, Benjamin M; Merkel, Tod; Scarpino, Samuel V; Koelle, Katia; Friedman, Lindsay; Arnold, Callum; Bolotin, Shelly
Abstract: We conducted a systematic review to describe the frequency of mild, atypical, and asymptomatic infection among household contacts of pertussis cases and to explore the published literature for evidence of asymptomatic transmission. We included studies that obtained and tested laboratory specimens from household contacts regardless of symptom presentation and reported the proportion of cases with typical, mild/atypical, or asymptomatic infection. After screening 6789 articles, we included 26 studies. Fourteen studies reported household contacts with mild/atypical pertussis. These comprised up to 46.2% of all contacts tested. Twenty-four studies reported asymptomatic contacts with laboratory-confirmed pertussis, comprising up to 55.6% of those tested. Seven studies presented evidence consistent with asymptomatic pertussis transmission between household contacts. Our results demonstrate a high prevalence of subclinical infection in household contacts of pertussis cases, which may play a substantial role in the ongoing transmission of disease. Our review reveals a gap in our understanding of pertussis transmission. Abstract : We identify a high prevalence of asymptomatic infection in the household contacts of pertussis cases that may play a prominent role in ongoing disease transmission. We also report evidence consistent with asymptomatic transmission as identified in human studies.